Teacher Empowerment to Prevent Oral Health Problems Related to Anemia in Adolescent Girls at SMPN 41 Surabaya - Lia Aulia Rachma; Lukas Aldhi Hannawan Siswoyo; Marselina Sesaria Pratiknjo; Muhammad Naufal Hatta; Gilang Rasuna Sabdho Wening; Sihombing, Manuel Raynaldy; Ni Nyoman Trisari Utami; Refibrianti Kusuma Maharani (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2023)
Background: An epidemiological study at SMPN 41 Surabaya revealed that approximately 50% of 7thand 8th-grade adolescent girls have poor daily eating behavior. Around 19 female students (63.3%) experience oral health problems related to anemia during menstruation. According to the Theory of Reasoned Action (TRA), subjective norms were found to have the most influence on forming intentions toward good daily eating behavior. Subjective norms refer to the influence or pressures from the surrounding environment. Within the school environment, teachers play a role as one of the subjective norms that affect the decision-making of female students regarding their daily eating behavior. Aims: To empower teachers to conduct examinations for anemia symptoms and clinical signs of oral health problems during menstruation among adolescent girls and to record their findings in the manual book. Methods: This program provides counseling and training on examining anemia symptoms and oral health problems to 23 teachers, utilizing a manual book as a medium. The effectiveness of the activity was evaluated using pre-test and post-test assessments. The scores obtained from both tests were analyzed using paired sample tests to assess the teachers' knowledge and skills improvement. Results: Based on the scores obtained from the pre-test and post-test assessments, it was found that the level of knowledge and skills of the teachers after the empowerment (Mean= 73.26; SD= 10.72) was higher compared to before the empowerment (Mean= 61.95; SD= 15.5). Statistically, it was determined that teacher empowerment significantly (p<0.05) improved their knowledge and skills in examining anemia symptoms and oral health problems. Conclusion: Empowering teachers through counseling and training significantly enhances their knowledge and abilities in examining anemia symptoms and oral health problems.